Refiguring Prose Style Possibilities For Writing Pedagogy - Johnson, T.R (University Press of Colorado, 2005)
For about two decades, say Johnson and Pace, the discussion of how to address prose style in teaching college writing has been stuck, with style standing in as a proxy for other stakes in the theory wars. The traditional argument is evidently still quite persuasive to some-that teaching style is mostly a matter of teaching generic conventions through repetition and practice. Such a position usually presumes the traditional view of composition as essentially a service course, one without content of its own. On the other side, the shortcomings of this argument have been much discussed-that it neglects invention, revision, context, meaning, even truth; that it is not congruent with research; that it ignores 100 years of scholarship establishing composition's intellectual territory beyond "service." The discussion is stuck there, and all sides have been giving it a rest in recent scholarship. Yet style remains of vital practical interest to the field, because everyone has to teach it one way or another. A consequence of the impasse is that a theory of style itself has not been well articulated. Johnson and Pace suggest that moving the field toward a better consensus will require establishing style as a clearer subject of inquiry. Accordingly, this collection takes up a comprehensive study of the subject. Part I explores the recent history of composition studies, the ways it has figured and all but effaced the whole question of prose style. Part II takes to heart Elbow's suggestion that composition and literature, particularly as conceptualized in the context of creative writing courses, have something to learn from each other. Part III sketches practical classroom procedures for heightening students' abilities to engage style, and part IV explores new theoretical frameworks for defining this vital and much neglected territory. The hope of the essays here-focusing as they do on historical, aesthetic, practical, and theoretical issues-is to awaken composition studies to the possibilities of style, and, in turn, to rejuvenate a great many classrooms.